Pulsed ultrasound modulated optical tomography utilizing the harmonic response of lock-in detection - Ruan, H.; Mather, M.L.; Morgan, Stephen P. (Optical Society of America, 2013)
Ultrasound modulated optical tomography (USMOT) can image the optical properties of a scattering medium at a spatial resolution approaching that of ultrasound (US). A lock-in parallel speckle detection technique is proposed to detect pulsed US modulated light using a multipixel detector. The frequency components of the pass band match those of the US pulse train and provide efficient detection. The modulation depth is extracted by taking the difference between a pair of speckle patterns modulated by a pair of phase-inversed US bursts. Modification to pulse inversion mode enables the second harmonic US modulation due to nonlinear US propagation to be detected. © 2013 Optical Society of America OCIS codes: (110.6150) Speckle imaging; (110.0113) Imaging through turbid media.